Digenetic trematodes - Fried, Bernard; Toledo, Rafael (Advances in Experimental Medicine and Biology,, 2014)
Digenetic trematodes constitute a major helminth group that parasitize humans and animals, and are a major cause of morbidity and mortality. The diseases caused by trematodes have been neglected for years, especially as compared with other parasitic diseases. However, the geographical limits and the populations at risk are currently expanding and changing in relation to factors such as growing international markets, improved transportation systems, and demographic changes. This has led to a growing international interest in trematode infections, although factors such as the difficulties entailed in the diagnosis, the complexity of human and agricultural practices, the lack of assessments of the economic costs, or the limited number of effective drugs are preventing the development of control measures of these diseases in humans and livestock. In-depth studies are needed to clarify the current epidemiology of these helminth infections and to identify new and specific targets for both effective diagnosis and treatments. The main goal of this book is to present the major trematodes and their corresponding diseases in the framework of modern parasitology, considering matters such as the application of novel techniques and analysis of data in the context of host-parasite interactions and to show applications of new techniques and concepts for the studies on digenetic trematodes. This is an ideal book for parasitologists, microbiologists, zoologists, immunologists, professional of public health workers, clinicians, and graduate and post-graduate students.